Efficient Inhibition of Streptococcus agalactiae by AIEgen-Based Fluorescent Nanomaterials - Yi, Mengmeng; Wang, He; Wang, Miao; Cao, Jianmeng; Gao, Fengying; Ke, Xiaoli; Liu, Zhigang; Liu, Ying; Lu, Maixin (Frontiers in Chemistry, 2021)
Streptococcus agalactiae (GBS) is an important co-pathogenic bacteria causing onset and death of human, animal and aquatic products. Although antibiotics are efficient for GBS, antibiotic resistance through antibiotic overuse is an equally serious problem. Therefore, the treatment of GBS infection appears strongly dependent on the non-antibiotic therapy, such as photodynamic therapy (PDT). Different from other photosensitizers, luminogens with aggregation-induced emission (AIE) can efficiently generate ﬂuorescence and reactive oxygen species (ROS) meanwhile. Herein, TBP-1, an efficient AIE PSs is chosen to resist GBS, and its antibacterial activity and the killing mechanism toward GBS are investigated. The ROS generation performance and the images of GBS treated with TBP-1 in darkness or white light irradiation were investigated. The TBP-1 with highly ROS generation can efficient kill GBS, and will serve as a novel strategy of treatment for GBS infection.